2015
DOI: 10.1002/bab.1341
|View full text |Cite
|
Sign up to set email alerts
|

Innovative approach for urease inhibition by Ficus carica extract–fabricated silver nanoparticles: An in vitro study

Abstract: In the present study, a rapid, low-cost, and ecofriendly method of stable silver nanoparticles (AgNPs) synthesis using leaves extract of Ficus carica (F. carica), a plant with diverse metabolic consortium, is reported for the first time. An absorption peak at 422 nm in UV-Vis spectroscopy, a spherical shape with an average size of 21 nm in transmission electron microscopy, and crystalline nature in X-ray powder diffraction studies were observed for the synthesized AgNPs. Fourier transform infrared analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…2C), which facilitated the stability of AgNPs. These patterns demonstrated that the AgNPs synthesized from wheat straw were face-centered cubic (FCC) structures, which coincides with previous studies (Borase et al 2015;Dhand et al 2016).…”
Section: Characterization Of Agnps Tem and Zeta Potential Analysissupporting
confidence: 91%
“…2C), which facilitated the stability of AgNPs. These patterns demonstrated that the AgNPs synthesized from wheat straw were face-centered cubic (FCC) structures, which coincides with previous studies (Borase et al 2015;Dhand et al 2016).…”
Section: Characterization Of Agnps Tem and Zeta Potential Analysissupporting
confidence: 91%
“…Usually, the activity of encapsulated enzymes decreased by a factor of 6-7 [1,6,[10][11][12][13][14][15]. Close results to our experimental data presented in this study on encapsulated urease were obtained in [16][17][18][19]. Authors, using the enzyme dextranase, obtained encapsulated enzymes with a catalytic activity equal to 80% of the activity of the free enzyme (the capsules were formed from calcium alginate with the inclusion of silica).…”
Section: Issn 2224-5308supporting
confidence: 79%
“…Ag-NPs have been obtained with sizes between 50 and 250 nm using Carica papaya leaf extract; 53 with average sizes 23±12, 32±24 and 19±22 nm using Illicium verum (star anise) seed extracts, 54 and average size 73 nm using an aqueous extract of Tephrosia tinctoria. 55 Regarding spherical shape homogeneity, our synthesis method was compared with that of other works where spherical Ag-NPs are synthesized, such as in the case of other green synthesis methods that employ leaf extracts of Saraca indica, 56 Ficus carica, 57 and Cocos nucifera. 58 The chemical and physical characterization of the Ag-NP samples suggests that the Acacia extract is capable of not only reducing the silver ions but also capping the Ag-NPs and stabilizing their surface.…”
Section: Discussion Synthesis and Characterization Of Ag-npsmentioning
confidence: 99%